Peramcangan dan Pemasangan Instalasi Listrik di SDQ Amirul Mukminin - Bagus Dwi Cahyono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Based on the results of initial observations at SDQ Amirul Mukminin, there were 4 classrooms that had not been installed with electrical installations according to standards. The community service activity consisted of 3 stages, namely: (1) Preparation Stage; ((2) Implementation Stage; and (3) Evaluation Stage. This activity lasted for 6 days, from 6–27 July 2024. The community service activity of Designing and Installing Electrical Installations at SDQ Amirul Mukminin which was carried out by the Electrical Engineering Vocational Education Study Program, Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University went well, with the results of the electrical installation having been installed according to standards at SDQ Amirul Mukminin